2019
DOI: 10.33594/000000139
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Antifungal Treatments of Caprylic Acid with Carvacrol or Thymol Induce Synergistic 6-Log Reduction of Pathogenic Candida albicans by Cell Membrane Disruption and Efflux Pump Inhibition

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Interestingly, in vitro analysis of fungal membrane fluidity upon treatment with CAP suggested large scale decrease in the bilayer order which was not seen upon exposure to LRA. This observation of fungal membrane perturbation by CAP aligns with existing literature reports of membrane damage caused by CAP in C. albicans and S. cerevisiae (Liu et al, 2013;Bae and Rhee, 2019). Further, our in vitro time kill assays and electron microscopy data show CAP and 2 http://www.who.int/mediacentre/factsheets/fs194/en/ its ester derivative, propylene glycol monocaprylate (PGMC), to have potent membrane disruptive actions against various fungal pathogens.…”
Section: Introductionsupporting
confidence: 89%
“…Interestingly, in vitro analysis of fungal membrane fluidity upon treatment with CAP suggested large scale decrease in the bilayer order which was not seen upon exposure to LRA. This observation of fungal membrane perturbation by CAP aligns with existing literature reports of membrane damage caused by CAP in C. albicans and S. cerevisiae (Liu et al, 2013;Bae and Rhee, 2019). Further, our in vitro time kill assays and electron microscopy data show CAP and 2 http://www.who.int/mediacentre/factsheets/fs194/en/ its ester derivative, propylene glycol monocaprylate (PGMC), to have potent membrane disruptive actions against various fungal pathogens.…”
Section: Introductionsupporting
confidence: 89%
“…This result suggests that our peptide could indirectly affect membrane integrity. It is widely reported that fatty acids, depending on their properties (i.e., chain length, degree, position and orientation of unsaturation) as well as those of their target, are able to interact with cell membranes ( Bhattacharyya et al, 2020 ), provoking structural perturbation and the consequent loss of functionality ( Liu et al, 2013 ; Bae and Rhee, 2019 ). The upregulation of genes encoding fatty acid synthases in treated P. oryzae cells correlates with membrane rearrangement of to form vesicles and autophagic bodies ( Polyansky et al, 2020 ), observed through the TEM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TEM images following singular treatments with CAR and NaCl showed disrupted membranes with damage to the cytoplasm and a decrease in the density of the cytoplasm, respectively. However, most of those cells maintained their morphological characteristics despite the slight increases in damaged cells observed by flow cytometry, highlighting that membrane damage caused by singular treatments using low quantity of EOs with short-term exposure was reversible and insufficient for affecting viability [9]. The combined treatments showed evidence of irreversible damage or cell death by both analytical methods (flow cytometry and TEM) based on the increases in the population of damaged/dead cells and highly deformed membranes allowing the leakage of cellular material from the cells, respectively.…”
Section: Antimicrobial Mechanisms Of Eo Complex Against Pathogensmentioning
confidence: 94%
“…In addition, EOs have been shown to have antibacterial [6,7], antifungal [8,9], antiviral [10], antimycotic [11], antiparasitic [12], and insecticidal activities [13]. Along with the drastically increased interests from consumers in the use of natural agents for the development of antimicrobial products (e.g., disinfectants, preservatives, and food additives), natural compounds including EOs are preferred and the role of EOs as alternatives to synthetic chemical agents has been emphasized [14][15][16].…”
Section: Introductionmentioning
confidence: 99%